Design and Development of Tangram-Based Educational Games to Enhance Creativity in Early Childhood - Melta Santri Hardila; Rakimahwati Rakimahwati (Suluah Pasaman, 2026)
This study aimed to develop a tangram-based educational game designed to stimulate creativity and introduce geometric concepts among early childhood learners. The study employed a Research and Development (R&D) approach using the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. Data were collected through observation, interviews, questionnaires, documentation, and tests. Validity, practicality, and effectiveness were assessed using structured questionnaires administered to content and media experts, as well as end-users. Validation results demonstrated that the educational game met the validity criteria, with a content expert score of 93.3% and a media expert score of 89.41%. The practicality assessment yielded an average score of 91%, indicating that the game is feasible for classroom implementation. The effectiveness evaluation resulted in a score of 93%, confirming that the game significantly supported children's learning outcomes. These findings suggest that the tangram-based educational game is valid, practical, and effective as an instructional tool for early childhood education. The study contributes to the growing body of literature on game-based learning and hands-on instructional media in early childhood settings